Measurement of the magnitude of force applied by students when learning a mobilisation technique - E. Smit; M. Conradie; J. Wessels; I. Witbooi; R. Otto (AOSIS, 2003)
Passive accessory intervertebral movements (PAIVM's) are frequently used by physiotherapists in the  assessment and management of patients. Studies investigating the reliability of passive mobilisation techniques have shown conflicting results. Therefore, standardisation of PAIVM's is essential for research and teaching purposes, which could result in better clinical management. In order to standardise graded passive mobilisation techniques, a reliable, easy-to-use, objective measurement tool must be used. The aim of this  study was to determine whether it is necessary to quantify the magnitude of force applied when teaching a grade I central  posteroanterior (PA) mobilisation technique (according to Maitland) on the cervical spine. An objective measurement tool (FlexiForceTM) was used to determine the consistency of force applied by third and fourth year physiotherapy students while performing this technique. Twenty third- and 20 fourth year physiotherapy students (n=40) were randomly selected. Each subject performed a grade I central PA on sensors placed on C6 for 25 seconds. The average maximum grade 1 force applied by the third year students was  significantly higher than the force applied by the fourth year students (p=0.034). There was a significantly larger variation in applied force among third years (p=0.00043). The results indicate that the current teaching method is insufficient to ensure inter-therapist reliability amongst students, emphasising the need for an objective measurement tool to be used for teaching students. The measurement tool used in this study is economical, easily applied and is an efficient method of measuring the magnitude of force. Further research is needed to demonstrate the reliability and validity of the tool to assist teaching and research in a clinical setting.